2006
DOI: 10.2164/jandrol.05089
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins in the Accessory Sex Gland Fluid Associated With Fertility Indexes of Dairy Bulls: A Proteomic Approach

Abstract: ABSTRACT:We evaluated the expression of proteins in the accessory sex gland fluid (AGF) and their relationships with fertility indexes of dairy bulls. Fertility was normalized as the percentage point deviation of their nonreturn rates (PD) from the average fertility of all bulls from a given artificial insemination center. Services associated with each sire ranged from 269 to 77 321 and PD values from ϩ7.7% to Ϫ18.1%. AGF, from 37 bulls, was obtained with an artificial vagina after cannulation of the vasa defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
174
0
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(192 citation statements)
references
References 42 publications
9
174
0
9
Order By: Relevance
“…The specific role played by PGDS in male fertility is still a matter of speculation, but it has been suggested that it works as a transporter of lipophilic substances, such as retinol, across testis/epididymal-blood barriers and to the sperm (Leone et al, 2002). Negative relationships exist between the intensity of PGDS spots detected in the CEF 2-D electrophoresis maps and non-return rates of dairy bulls (Moura et al, 2006a), while positive associations were detected between PGDS spot intensity in 2D maps of seminal plasma and bull fertility (Killian et al, 1993). Other researchers found positive correlations between seminal plasma PGDS and sperm motility in the man (Chen et al, 2005;2007a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The specific role played by PGDS in male fertility is still a matter of speculation, but it has been suggested that it works as a transporter of lipophilic substances, such as retinol, across testis/epididymal-blood barriers and to the sperm (Leone et al, 2002). Negative relationships exist between the intensity of PGDS spots detected in the CEF 2-D electrophoresis maps and non-return rates of dairy bulls (Moura et al, 2006a), while positive associations were detected between PGDS spot intensity in 2D maps of seminal plasma and bull fertility (Killian et al, 1993). Other researchers found positive correlations between seminal plasma PGDS and sperm motility in the man (Chen et al, 2005;2007a).…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of selected protein spots in 2-D maps of seminal plasma (Killian et al, 1993), accessory sex gland fluid (Moura et al, 2006a) and cauda epididymal fluid (Moura et al, 2006b) is related to the fertility of dairy bulls as well. Furthermore there is a relationship of these proteins with the in vitro penetration of bovine oocytes (Moura et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…La cantidad relativa de cada banda (entre 26 y 22%) y su aparición en todas las fracciones, demostrada en la electroforesis unidimensional, indicó que estas proteínas son las más abundantes dentro del PS. En este sentido se ha evidenciado que las proteínas BSP, son las más abundantes en el PS bovino (2,19,22,23). La concentración de estas proteínas en el PS está entre 20 y 40 mg/ml, lo que corresponde a una concentración de entre el 30 y el 60% de las proteínas totales del PS.…”
Section: Discussionunclassified